Adolescents as theologians: a new approach in Christian education and youth ministry - Schweitzer, Friedrich (Religious education, 2014)
The author argues that adolescents are not only philosophers, as Kohlberg and Gilligan once claimed, but should also be viewed as theologians. This view corresponds to what has been called “lay theology” or “ordinary theology.” Moreover, the article takes up the double question what adolescents might benefit from theology and what theology might benefit from adolescents. On this background, a systematic understanding of adolescents as theologians is offered, distinguishing between theology of adolescents, with adolescents, and for adolescents. In a final section, theological views concerning adolescence as a stage in the human lifecycle are discussed.